Simulating micelle self-assembly to assess potential for viscosity build in surfactant formulations - Lavagnini, Ennio; Booth, Jonathan; Helm, Katy; El-Benni, Ferdaous; Warren, Patrick B.; Bray, David J.; Anderson, Richard L. (Frontiers in Soft Matter, 2024)
Self-assembly of surfactants into complex structures is key to the performance of many formulated products, which form a significant fraction of the world's manufactured goods. Here we adopt the dissipative particle dynamics simulation approach to explore the self-assembly process of surfactants, with the aim of understanding what information can be obtained that may correlate with an increased zero-shear viscosity of surfactant based products. To this end we experimentally measured the zero-shear viscosity of mixed micelle systems comprised of cocoamidopropyl betaine (CAPB) and sodium lauryl sarcosinate (SLSar), as a function of the CAPB / SLSar mass ratio and pH, and characterised the early stages of self-assembly of the same systems computationally. From simulation we identify three distinct behaviors in the micellar self-assembly process (logarithmic, linear and cubic growth) which we find show some degree of correlation with the experimental zero-shear viscosity. Owing to the relatively short simulation times required, this may provide formulation scientists with a practical route to identify regions of interest (i. e. those with a desired zero-shear viscosity) prior to synthesising de novo (potentially natural) surfactants.